'We're all in the same boat': An Interpretative Phenomenological Analysis study of experiences of being an 'expert' during patient and public involvement within Child and Adolescent Mental Health Services (CAMHS). (2nd February 2021) - Idrees, Samiran; Hartley, Samantha; Hearn, Jasmine Heath
Abstract: Background: Patient and Public involvement (PPI) has rapidly evolved into a key component in shaping the delivery of health services. However, little is known about what it is like to participate in involvement procedures that include representatives of multiple groups and in the context of developing new interventions for Child and Adolescent Mental Health Services (CAMHS). Objective: This study explored participants' experiences of PPI, following attending a 'consensus conference', during which their views were sought in relation to the development of a proposed staff‐based intervention and key questions about its design and implementation. Design: Qualitative, semi‐structured interview study. Setting and Participants: Six participants, including service users and various frontline clinical staff team members, who had experience of CAMHS were present at the consensus conference and then asked about their experiences of being involved via semi‐structured interviews. The data were analysed using Interpretative Phenomenological Analysis (IPA). Young people, carers and frontline staff have been involved in the design and implementation throughout the broader programme of work of which this study forms part, although these groups were not directly involved in the design and implementation of this paper. Results: Three key narratives were present: (a) Previous Experiences Driving Expectations, (b) 'We are all in the same boat' and (c) The Realization of Multiple Identities. The results suggest that PPI involvement is a complex process that may be driven by positive/negative expectations, but that individuals value learning about others and recognizing different perspectives while reaching shared goals in improving services. Discussion and Conclusion: This study demonstrates the complexity of experience that service users and clinical staff face when engaging in involvement activities in CAMHS. The findings demonstrate the value in engaging multiple stakeholder groups while also highlighting the importance of proper consideration of the procedures involved and facilitators of engagement.